2005
DOI: 10.1111/j.1651-2227.2005.tb02152.x
|View full text |Cite
|
Sign up to set email alerts
|

Increase of faecal bifidobacteria due to dietary oligosaccharides induces a reduction of clinically relevant pathogen germs in the faeces of formula‐fed preterm infants

Abstract: In a previous study on formula‐fed preterm infants, we were able to demonstrate that dietary oligosaccharides (a mixture of 90% galacto‐oligosaccharides and 10% fructo‐oligosaccharides in a concentration of 1 g/dl) stimulate the growth of faecal bifidobacteria. In the present explorative analysis of this study, we focus on the effect of the dominance of bifidobacteria on the presence of clinically relevant pathogens (Staphylococcus aureus, Staphylococcus epidermidis, Staphylococcus haemolyticus, Pseudomonas ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 3 publications
1
51
1
2
Order By: Relevance
“…The most notable dietrelated differences in bacterial assemblages were the greater intensities for the T-RF 233 and 583-bp bands in the distal SI of the FORM pigs. The T-RF 233-bp band corresponds with Clostridium perfringens, which has been implicated as a causative agent of NEC (19), and the greater band intensity is consistent with the higher clostridial densities associated with formula feeding (25). The 583-bp band includes several Streptococcus species, with some considered as potential pathogens (38), whereas others have probiotic properties (9).…”
Section: Discussionmentioning
confidence: 95%
“…The most notable dietrelated differences in bacterial assemblages were the greater intensities for the T-RF 233 and 583-bp bands in the distal SI of the FORM pigs. The T-RF 233-bp band corresponds with Clostridium perfringens, which has been implicated as a causative agent of NEC (19), and the greater band intensity is consistent with the higher clostridial densities associated with formula feeding (25). The 583-bp band includes several Streptococcus species, with some considered as potential pathogens (38), whereas others have probiotic properties (9).…”
Section: Discussionmentioning
confidence: 95%
“…Preliminar y studies show increased Bifidobacterium stool colonization and decreased pathogenic bacterial colonization in preterm infants fed with formula containing prebiotics (90% short chain galacto-oligosaccharide, 10% long chain fructo-oligosaccharide) compared with infants fed control formula [167] . Furthermore, prebiotic treatment may have a positive effect on host immune function [168] .…”
Section: Prebioticsmentioning
confidence: 99%
“…Some studies have reported that the addition of prebiotics to the diet results in increased levels of bifidobacteria and lactobacilli in the intestinal flora (30,31). The effects of prebiotics, including inulin, have been extensively investigated in infant nutrition studies; stool properties of infants receiving prebiotics are similar to those of breastfed infants (32).…”
Section: Placebo Groupmentioning
confidence: 99%